EFEKTIVITAS SOSIALISASI SURVEI SOSIAL EKONOMI NASIONAL (SUSENAS) TAHUN 2020 OLEH BPS TERHADAP MASYARAKAT ACEH BARAT DAYA - khartika, nur safridha; darman, su (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2021)
The purpose of this study was to determine the effectiveness of the socialization of the 2020 National Socio-Economic Survey (Susenas) by BPS to the people of Aceh Barat Daya. This research also looks at the process of social approach to the community, how officers and supervisors communicate with the community, what are the conditions and situation in the field. This study uses qualitative methods with data collection techniques using interviews. The data collected consisted of primary data, namely from information obtained from enumerators and supervisors in the field. The conclusion of this research is that there is an effectiveness of SUSENAS socialization conducted by BPS to the people of Aceh Barat Daya. The effectiveness can be seen from the level of community participation to 100% in SUSENAS in September 2020, compared to March the community participation rate of 98.2%. This shows that the role of SUSENAS socialization in the achievement of data on the people of  Aceh Barat Daya by BPS has reached the target of effectiveness with an increase in September.